Has the Swap Influenced Aid Flows in the Health Sector?. (11th March 2015) - Sweeney, Rohan; Mortimer, Duncan
Abstract: The sector wide approach (SWAp) emerged during the 1990s as a mechanism for managing aid from the multiplicity of development partners that operate in the recipient country's health, education or agricultural sectors. Health SWAps aim to give increased control to recipient governments, allowing greater domestic influence over how health aid is allocated and facilitating allocative efficiency gains. This paper assesses whether health SWAps have increased recipient control of health aid via increased general sector‐support and have facilitated (re)allocations of health aid across disease areas. Using a uniquely compiled panel data set of countries receiving development assistance for health over the period 1990–2010, we employ fixed effects and dynamic panel models to assess the impact of introducing a health SWAp on levels of general sector‐support for health and allocations of health‐sector aid across key funding silos (including HIV, 'maternal and child health' and 'sector‐support'). Our results suggest that health SWAps have influenced health‐sector aid flows in a manner consistent with increased recipient control and improvements in allocative efficiency. Copyright © 2015 John Wiley & Sons, Ltd.